2020
DOI: 10.1016/j.socscimed.2020.113261
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resilience, depression, anxiety, and somatization symptoms in response to COVID-19: A study of the general population in China at the peak of its epidemic

Abstract: Rationale Psychological resilience is characterized as the ability to respond to extreme stress or trauma or adverse experience successfully. While the relation between public emergencies and psychological distress is well known, research on therelationship between psychological resilience and mental health is very limited during the outbreak of public health emergencies. Objective This research investigated the relationship between psychological resilience and mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
286
5
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(343 citation statements)
references
References 39 publications
28
286
5
24
Order By: Relevance
“…In the midst of the COVID-19 pandemic, a slew of recent studies has shown that resilient healthcare professionals experienced lower anxiety, posttraumatic stress, and depression (33,34). Among the general populace, similar patterns emerged (30,32,35,36). In other words, those who were able to adaptively cope with COVID-19 related stressors were better equipped to attenuate the onset of emotional distress consequences (37,38).…”
Section: Resilience and Depressionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the midst of the COVID-19 pandemic, a slew of recent studies has shown that resilient healthcare professionals experienced lower anxiety, posttraumatic stress, and depression (33,34). Among the general populace, similar patterns emerged (30,32,35,36). In other words, those who were able to adaptively cope with COVID-19 related stressors were better equipped to attenuate the onset of emotional distress consequences (37,38).…”
Section: Resilience and Depressionmentioning
confidence: 97%
“…Alternative Models I-II were direct derivatives of the proposed conceptual model but made strong assumptions that depressive symptoms were not directly preceded by resilience (Model I) and epidemic rumination (Model II). Both alternative models yielded comparable fits but ultimately did not allow for incorporating past findings that implicate direct effects of rumination [e.g., (15,25)] and resilience on depressive symptoms [e.g., (30,32,35,36)]. Further, consistent with prior evidence of resilience as a moderating trait [e.g., (26,67)], Alternative Models IV-VIII were also examined in which rumination was tested as a moderator at multiple paths.…”
Section: Considering Alternative Modelsmentioning
confidence: 99%
“…Thousands of people have lost their work and socio-economic status during the COVID-19 pandemic. Numerous studies have reported an increase in anxiety and depression among people around the world [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A review study indicated that, up to the time of its publishing, the prevalence of anxiety and depression ranged between 16-28% of the Chinese population during the COVID-19 pandemic [13].…”
Section: Mental Health During the Covid-19 Pandemicmentioning
confidence: 99%
“…O mundo vivenciou, em 2019, o início de uma grande crise psicossocial causada pela doença do coronavírus 2019 (Coronavirus disease 2019 -COVID- 19), síndrome respiratória aguda ocasionada pelo novo coronavírus (novel Coronavirus -2019-nCoV), inicialmente detectada na cidade de Wuhan, capital da província da China Central, de onde rapidamente atingiu quase todos os países do mundo. Isso, então, provocou uma pandemia, considerada a maior emergência em saúde enfrentada pelo mundo em décadas (Ran et al, 2020;Schmidt et al, 2020;Xiao, 2020). No Brasil, até 28 de outubro deste ano, 5.468.270 casos foram notificados e 158.456 óbitos por COVID-19, confirmados (Brasil, 2020).…”
Section: Introductionunclassified
“…As palavras "comunidade e resiliência a desastres são, na prática, termos sinônimos. Ambos são conceitos inclusivos e holísticos" (Castleden et al, 2011;Makwana, 2019;Ran et al, 2020).…”
Section: Introductionunclassified